2019
DOI: 10.1111/1750-3841.14733
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of N‐(1‐Deoxy‐Α‐D‐Xylulos‐1‐Yl)‐Glutamic Acid via Aqueous Maillard Reaction Coupled with Vacuum Dehydration and Its Flavor Formation Through Thermal Treatment of Baking Process

Abstract: Amadori rearrangement product (ARP) derived from glutamic acid (Glu) and xylose (Xyl) was prepared by aqueous Maillard reaction. Subsequently, ion exchange chromatography, MS, and NMR were used for purification and identification, confirming that the molecular formula of ARP was C10H17NO8, namely N‐(1‐deoxy‐α‐D‐xylulos‐1‐yl)‐glutamic acid, with a molecular mass of 279 Da. To improve the aqueous yield of ARP, a thermal reaction coupled with vacuum dehydration was used and the yield of ARP was increased from 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…The sulfhydryl group (‐SH) of cysteine has the strong reactivity to interact with MGX and other reactive compounds to form adducts (Huang et al., ). Therefore, the interaction between ‐SH and MGX would change the pathway of Maillard reaction and inhibit the formation of melanoidins (Xu et al., ; Yang et al., ). The minimum A 420 might be the sign for the formation of the MGX.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfhydryl group (‐SH) of cysteine has the strong reactivity to interact with MGX and other reactive compounds to form adducts (Huang et al., ). Therefore, the interaction between ‐SH and MGX would change the pathway of Maillard reaction and inhibit the formation of melanoidins (Xu et al., ; Yang et al., ). The minimum A 420 might be the sign for the formation of the MGX.…”
Section: Resultsmentioning
confidence: 99%
“…According to the mechanism of the Maillard reaction, the carbonyl group of xylose reacts with the amino group of amino acid to form N-substituted d -xylosamine through an addition reaction and then dehydrate via a β-elimination reaction to form a Schiff base followed by molecular rearrangement, yielding the ARP (Figure ). Xu et al prepared the glutamic acid–xylose ARP in aqueous medium, the yield of ARP was only 1.85%. Similarly, the yields of proline–glucose, phenylalanine–xylose, and glycine–xylose systems were also only 3.63, 13.62, and 1.44%, respectively. On the other hand, the method of preparing ARPs in the organic phase requires the application of large amounts of methanol as a solvent, which leads to serious pollution and high technical costs and could not be applied in modern industrial production. …”
Section: Introductionmentioning
confidence: 99%
“…5−7 According to the mechanism of the Maillard reaction, the carbonyl group of xylose reacts with the amino group of amino acid to form N-substituted D-xylosamine through an addition reaction and then dehydrate via a β-elimination reaction to form a Schiff base followed by molecular rearrangement, yielding the ARP (Figure 1). 8−11 Xu et al 12 prepared the glutamic acid−xylose ARP in aqueous medium, the yield of ARP was only 1.85%. Similarly, the yields of proline−glucose, phenylalanine−xylose, and glycine−xylose systems were also only 3.63, 13.62, and 1.44%, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because TTCA seems to be stable because of its ring structure, the chemical equilibrium may be favorable to the TTCA side, which can circumvent the transformation from TTCA to ARP as well as the development of downstream products. , Consequently, it may be not suitable for some food systems requiring the rapid generation of ideal colors or other sensory characteristics. Hence, it is of great importance to regulate the degradation rate of TTCA in order to make it fit for different food processing conditions, which is beneficial to the advancement of processing adaptability of TTCA . Based on this, a recent research indicated that as compared to TTCA alone, a mixture of TTCA and amino acids (such as glycine) revealed a higher reactivity for the development of both melanoidins and flavors .…”
Section: Introductionmentioning
confidence: 99%
“…At the initial stage of the MR, amino acids act as the “catalysts” of enolization, rearrangement, and cleavage reaction. , During the late stage of the reaction, they can be involved in the formation of flavors and colors through Strecker degradation, including decarboxylation, transamination, oxidation, cyclization, and subsequent polymerization . Deng et al found that the amino acid released from ARP showed an upward trend under the thermal reaction conditions of pH 5.5 and 7.5 at 100 °C and maintained for 4 h. This fact might be ascribed to the low reactivity of released amino acids or less short-chained α-dicarbonyl compounds formed to react with them.…”
Section: Introductionmentioning
confidence: 99%